Spherical array self-mixing oscillator antenna - Krairiksh, M.; Buasomboon, W.; Ngamjanyaporn, P.; Phongcharoenpanich, C. (My University, 2002)
A spherical array self-mixing oscillator antenna is designed by applying the injection locking technique to the spherical array of Gunn diode mounted waveguide radiators. The beam steering with considerably constant pattern and low cross-polarisation can be accomplished without using the sophisticated phase shifters. This antenna is designed and tested at the frequency of 10 GHz.